2021
DOI: 10.1016/j.pediatrneurol.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-d-Aspartate Receptor Encephalitis Associated With COVID-19 Infection in a Toddler

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 10 publications
1
64
0
11
Order By: Relevance
“…Monti et al [ 6 ] reported a 50-year-old patient with status epilepticus, anti-NMDAR antibody, and COVID-19 rtPCR positivity but no respiratory or systemic symptoms; Panariello et al [ 4 ] described a 23-year-old boy with acute psychosis due to anti-NMDAR encephalitis, also with no respiratory system involvement. Younger patients with anti-NMDAR encephalitis and COVID-19 positivity were reported by Burr et al [ 5 ] and Moideen et al [ 7 ] in 23 months and 17-year-old patients, respectively, the latter with acute psychosis. Our patient, unlike those in other reports, manifested with acute ataxia, only to become encephalopathic over days.…”
Section: Discussionmentioning
confidence: 77%
“…Monti et al [ 6 ] reported a 50-year-old patient with status epilepticus, anti-NMDAR antibody, and COVID-19 rtPCR positivity but no respiratory or systemic symptoms; Panariello et al [ 4 ] described a 23-year-old boy with acute psychosis due to anti-NMDAR encephalitis, also with no respiratory system involvement. Younger patients with anti-NMDAR encephalitis and COVID-19 positivity were reported by Burr et al [ 5 ] and Moideen et al [ 7 ] in 23 months and 17-year-old patients, respectively, the latter with acute psychosis. Our patient, unlike those in other reports, manifested with acute ataxia, only to become encephalopathic over days.…”
Section: Discussionmentioning
confidence: 77%
“…Increased expression of NMDARs occurs in a variety of cancers such as neuroblastoma, breast, small-cell lung, and ovarian cancer(39). Anti-NMDAR encephalitis, characterized by abnormal neurological and behavioral symptoms, has been reported in both COVID-19 and HSV(40). Notably, HSV can lead to an increased cervical cancer risk(41, 42).…”
Section: Resultsmentioning
confidence: 99%
“…We read with great interest the article by Burr et al on NMDA- receptor encephalitis associated with COVID-19 infection. 1 Although Anti-NMDAR encephalitis has been associated with COVID-19 in adults, this is the first report in a child. 2 With initial evidence for COVID-19 in children suggesting an asymptomatic or mild course in most, the identification and management of novel clinical presentations become even more relevant.…”
mentioning
confidence: 79%